Perspective on Carbon Anode Materials for K+ Storage: Balancing the Intercalation‐Controlled and Surface‐Driven Behavior. Issue 29 (12th June 2021) - Yang, Jiaying; Zhai, Yixuan; Zhang, Xiuhai; Zhang, En; Wang, Hongqiang; Liu, Xingrui; Xu, Fei; Kaskel, Stefan
Abstract: Potassium‐ion batteries (PIBs) have emerged as a compelling complement to existing lithium‐ion batteries for large‐scale energy storage applications, due to the resource‐abundance of potassium, the low standard redox potential and high conductivity of K + ‐based electrolytes. Rapid progress has been made in identifying suitable carbon anode materials to address the sluggish kinetics and huge volume variation problems caused by large‐size K + . However, most research into carbon materials has focused on structural design and performance optimization of one or several parameters, rather than considering the holistic performance especially for realistic applications. This perspective examines recent efforts to enhance the carbon anode performance in terms of initial Coulombic efficiency, capacity, rate capability, and cycle life. The balancing of the intercalation and surface‐driven capacitive mechanisms while designing carbon structures is emphasized, after which the compatibility with electrolyte and the cell assembly technologies should be considered under practical conditions. It is anticipated that this work will engender further intensive research that can be better aligned toward practical implementation of carbon materials for K + storage. Abstract : For developing advanced carbon anode materials in potassium‐ion batteries, it is vital to well balance the diffusion‐controlled intercalation and surface‐driven capacitive mechanisms. Consequently, comprehensive optimization of initial Coulombic efficiency, capacity, rate capability, cycle life, and low‐potential plateau discharge/charge curves could be realized to be better aligned toward practical implementation of carbon materials for K + storage.